2020
DOI: 10.25259/sni_635_2020
|View full text |Cite
|
Sign up to set email alerts
|

Can awake glioma surgery be the new standard of care in developing countries?

Abstract: Part of the Neurology Commons, Neurosurgery Commons, and the Surgery Commons International • 2020 • 11(434) | 1 is is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-Share Alike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms. Surgical Neurology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…AC provides many advantages compared with surgery under general anesthesia (GA) by enabling real-time cortical and subcortical brain mapping under local anesthesia. 4,22-28 In the awake-awake-awake approach, the patient is sedated at light, moderate, or deep levels with spontaneous ventilation during craniotomy and closure. 6,29,30 Although in the asleep-awake-asleep approach, the patient is under GA with a laryngeal mask airway/endotracheal intubation during craniotomy and closure and awakened and extubated during the mapping and resection step in.…”
mentioning
confidence: 99%
“…AC provides many advantages compared with surgery under general anesthesia (GA) by enabling real-time cortical and subcortical brain mapping under local anesthesia. 4,22-28 In the awake-awake-awake approach, the patient is sedated at light, moderate, or deep levels with spontaneous ventilation during craniotomy and closure. 6,29,30 Although in the asleep-awake-asleep approach, the patient is under GA with a laryngeal mask airway/endotracheal intubation during craniotomy and closure and awakened and extubated during the mapping and resection step in.…”
mentioning
confidence: 99%
“…Glioma is regarded as one of the dominant causes of cancer globally, and its pathological complexity necessitates combination therapies of various therapeutic elements, such as anti-cancer drugs and genes, to achieve synergistic treatment [ 4 , 5 , 20 ]. REV7 is an important subunit of pol ζ and is highly evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, glioma has become one of the most commonly diagnosed types of cancer worldwide [1][2][3]. With the recurrence and metastasis ability of cancer cells, the number of patients diagnosed with malignant glioma is increasing [3][4][5]. Current anti-glioma therapies include chemotherapy and surgery, and previous research has shown that chemotherapy can improve the lifespan and quality of life of most glioma patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Awake craniotomies have shown to promote a better extent of resection, a lower risk of new deficits, and improved progression-free survival among patients. 3 Histologically, astrocytomas and oligodendrogliomas are the two most common subtypes of LGGs, and can be further characterized by molecular genotypes and growth patterns. 4 Oligodendrogliomas are characterized by both an isocitrate dehydrogenase (IDH) mutation and chromosomal 1p and 19q co-deletions, and have an encouraging prognosis.…”
Section: Introductionmentioning
confidence: 99%